2006
DOI: 10.1097/01.hjh.0000209988.51606.c7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in sodium balance on plasma and kidney angiotensin II levels in anesthetized and conscious Ren-2 transgenic rats

Abstract: On the basis of our present results we conclude that TGR exhibit a disrupted interaction between sodium homeostasis and the regulation of the renin-angiotensin system (RAS) activity which results in the loss of BP regulation in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 66 publications
4
67
0
Order By: Relevance
“…Conflicting data concerning ANG II concentrations in TGR were reported, showing either similar [8] or higher [31,32] plasma concentrations. The finding of similar concentrations of ANG II in anesthetized TGR and HanSD rats in the present study are fully in accordance with our previous study showing strong differences in plasma and kidney concentrations of ANG II between conscious and anesthetized animals [33] . Finally, the increased plasma and decreased kidney ANG II levels in TGR continuously treated with candesartan show that candesartan is an effective antihypertensive agent resembling other AT 1 receptor antagonists [32] .…”
Section: Discussionsupporting
confidence: 94%
“…Conflicting data concerning ANG II concentrations in TGR were reported, showing either similar [8] or higher [31,32] plasma concentrations. The finding of similar concentrations of ANG II in anesthetized TGR and HanSD rats in the present study are fully in accordance with our previous study showing strong differences in plasma and kidney concentrations of ANG II between conscious and anesthetized animals [33] . Finally, the increased plasma and decreased kidney ANG II levels in TGR continuously treated with candesartan show that candesartan is an effective antihypertensive agent resembling other AT 1 receptor antagonists [32] .…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, there are studies that reported that plasma and tissue ANG II concentrations are significantly higher in hypertensive TGR than in normotensive HanSD rats [11][12][13][14][15][16] , suggesting that enhanced formation of ANG II is the main pathophysiological mechanism responsible for the development and maintenance of hypertension in this model. Whereas it is difficult to reconcile these contradictory results, we found in our recent study [17] first that anesthesia increases plasma and kidney ANG II levels in HanSD rats to a greater extent than in TGR and second that in conscious rats, i.e. when samples were harvested immediately after decapitation, plasma and tissue ANG II concentrations in male heterozygous TGR were higher than in HanSD rats.…”
Section: Introductionmentioning
confidence: 66%
“…when samples were harvested immediately after decapitation, plasma and tissue ANG II concentrations in male heterozygous TGR were higher than in HanSD rats. In addition, we found that male TGR display a lack of appropriate responses of plasma and kidney ANG II levels to changes in salt balance [17] . Moreover, we have recently found that other ANG II-dependent rat models such as 2-kidney, 1-clip Goldblatt and ANG II-infused hypertensive rats responded to anesthesia by markedly lower increases in plasma and kidney ANG II levels than normotensive rats [18] .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations